The dynamic interactions between cellular-molecular physiology and the environment - the cellular-molecular approach to evolution as niche construction - Torday, John S. (Henry Stewart Talks, 2016)
Niche construction: definitions and examples, The endomembrane system, Advent of cholesterol depended on oxygen, Ecosystems and the process of death, Internal niche construction, The swim-bladder, the lung and PTHrP, Niche construction and epigenetics interactions, Gaia hypothesis